Adapting sweetpotato production to changing climate in Mozambique - Makunde, G.S.; Andrade, M.I.; Menomussanga, J.; Grüneberg, W.J. (Walter de Gruyter GmbH, 2018)
Vines are the major source of planting material in sweetpotato. Extended dry spells hinder conservation of vines and in turn affect the availability of planting material at the onset of rains in southern Africa. In some cases, improved sweetpotato germplasm has been lost by smallholder farmers in Mozambique due to prolonged dry spells. Small to medium roots provide an opportunity to conserve germplasm and get planting material at the beginning of the rainy season. The objectives of the study were to (i) measure sprouting ability of diverse germplasm of sweetpotato - farmer varieties, improved clones and released varieties and (ii) estimate their ability to provide planting material for the next crop in southern Mozambique. Trials with 29 genotypes were established in a randomized complete block design with two replications at Umbeluzi Research Station and Nwalate Farm in 2015, 2016 and 2017. At harvest, 14 small to medium roots were selected and stored in small plastic dishes filled with dry sand at Nwalate Farm. After four months in storage, 10 similar roots were taken and planted in 1 m row plots arranged in a randomized complete block design with two replications. The trials were irrigated to initiate sprouting and support plant growth during the first four weeks. Data collected were analysed using SAS 1996. All the tested genotypes sprouted after sowing. The number of sprouts per root were significantly affected by the genotype, location and genotype x location x year interactions. Caelan had the most sprouts per root. Sprout length measured at six weeks after sprouting was also significantly affected by genotype, location, year and genotype x location x year interactions. Caelan had vines each long enough to provide 10 cuttings of 10 cm length for rapid multiplication. The number of cuttings depended on the growth habit of the variety. Irene, a popular variety in Mozambique, is erect and bushy and could only provide four cuttings over the same period. Growth habit especially under a changing climate should be considered in breeding programs as an option of facilitating a sustainable and easy seed system.